Perancangan Sistem Manajemen Housekeeping Web Menggunakan Metode Agile - Demario, Demario; Ratnasari, Anita (Jurnal Ilmiah Sains dan Teknologi, 2026)
This study aims to design and develop a web-based housekeeping management system at Hotel Pinangsia to improve work efficiency, reporting accuracy, and staff coordination. The hotel faces several issues, including manual task scheduling, delayed room status reporting, and unintegrated inventory management. This research applies the Agile method using an iterative approach, which consists of data collection, sprint planning, system development, testing, and implementation stages. Data were gathered through observation, interviews, and documentation studies. The system was developed using PHP, MySQL, and Filament as the front-end framework. The implementation results show that the system can automate task scheduling, provide real-time room status reporting, and simplify inventory tracking. Functionality testing was carried out and received positive feedback from internal hotel users. The conclusion of this study is that the developed system significantly enhances the operational efficiency and service quality of housekeeping operations at Hotel Pinangsia.